POKUTIANYN’S JUG (a window to Yarema Hoyan’s studio) - Kachkan, V. A. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The author of the article reveals peculiarities of the artistic world of the laureate of Taras Shevchenko National Award Yaremy Hoyana.